Improving therapy of severe infections through drug repurposing of synergistic combinations. (October 2019) - Cheng, Yu-Shan; Williamson, Peter R; Zheng, Wei
Highlights: Drug combinations improve efficacy and permit dose reductions of each drug. Lowering the dose of combined drugs prevents concentration-associated toxicity. Drug combinations can overcome the growing resistance to antibiotics. Real-time screens, using patient isolates, identify treatments for severe infections. Drug repurposing and combinations can identify treatments for emerging pathogens. Abstract : Infections from multidrug resistant (MDR) pathogens and emerging viruses present challenges for effective clinical treatments. Drug repurposing and combination screens may provide therapies at a fraction of the time and cost of traditional methods of drug development. Synergistic combinations of two or three known compounds can increase therapeutic efficacy and reduce concentrations required for individual drugs, in turn, reducing the risk of drug toxicity. Using libraries of approved drugs, traditionally non-antibiotic compounds identified in repurposing screens can quickly move into clinical trials, since safety profiles have been previously established. Herein we summarize recent advances in identifying synergistic drug combinations and the use of drug screens for personalized medicine treatments of infections caused by MDR pathogens and emerging viruses.